PS02.144: ESOPHAGOPLASTY WITH FREE JEJUNUM FLAP AFTER COLON-ESOPHAGUS CONDUIT ISCHEMIA. (14th September 2018) - Papp, Andras; Vereczkei, Andras; Pavlovics, Gabor; Horvath, Ors
Abstract: Background: Colon interposition is mainly used as a second line treatment, when the stomach has to be resected for oncological or technical reasons, or when the stomach is deliberately kept intact for benign and congenital diseases in patients with long-life expectancy. Colon provides extended conduit length, reliable blood supply and low incidence of reflux. However, the early and late postoperative ischemic complication rate is 5–15%. Methods: Colon ischemia can frequently cause anastomosis complications, which can be safely treated with dilation or surgery. The most serious but rare complication is the acute conduit necrosis. More severe cases of necrosis require conduit take down with proximal esophageal diversion and placement of an enteral feeding tube. An uncommon complication is the colonic stricture due to chronic ischemia, which can be treated with conservative methods such as dilation and stenting. Surgery is indicated since the impaired deglutition can compromise the quality of life. Supercharged or free jejunal interposition is a suitable alternative conduit for esophageal replacement in patients with otherwise limited delayed reconstructive options. Good functional outcomes can be achieved despite the formidable technical challenges in this group of patients. Results: In three such cases, we could successfully use a free jejunal flap for reconstruction; the replacement type was different, using substernal, presternal and sternotomy routes. The arterial blood supply was provided by the internal mammary artery. Saphenous graft was used to interconnect to external jugular or innominate vein to reestablish the venous drainage. All three patients survived without further complication. Conclusion: Overall, it can be stated that free jejunal graft transplantation can be used to resolve complicated cases that cannot be reconstructed with any other methods and jejunum offers a good swallowing function and quality of life. Disclosure: All authors have declared no conflicts of interest.